Investigating the role of delayed contrast magnetic resonance imaging (MRI) to differentiate radiation necrosis from tumour recurrence in brain metastases after stereotactic radiosurgery. Issue 3 (17th January 2023) - Admojo, Lorenztino; Korte, James; Anderson, Nigel; Phillips, Claire; Caspersz, Lauren; Lasocki, Arian
Abstract: Introduction: The incidence of radionecrosis (RN) after stereotactic radiosurgery (SRS) to brain metastases is increasing. An overlap in the conventional MRI appearances of RN and tumour recurrence (TR) is diagnostically challenging. Delayed contrast MRI compares contrast enhancement over two time periods to create treatment response assessment maps (TRAMs). We aim to assess the utility of TRAMs in brain metastases patients. Methods: Delayed contrast MRI scans were performed on ten brain metastases patients, previously treated with SRS, who developed equivocal lesion(s) on routine MRI follow‐up. T1‐weighted images were obtained five minutes and 60–75 min after contrast injection, followed by Brain Lab software analysis to create TRAMs. TRAMs patterns were then compared with the patient's clinical status, subsequent imaging, and histology results. Results: We identified three regions on TRAMs: central, peripheral, and surrounding. Each region could be described either as contrast accumulation (red colour and representing non‐tumour tissue) or contrast clearance (blue colour and representing tumour tissue). Our analysis demonstrated similarities in the TRAMs pattern between TR and RN, though to varying degrees. Conclusion: In conclusion, the TRAMs appearances of RN and TR overlap. Our findings suggest that the previously‐described correlation between contrast clearance and TR is at least partially attributable to more solid initial enhancement, rather than convincingly a difference in the underlying tissue properties, and the additional diagnostic value of TRAMs may be limited. Thus, further research on TRAMs is necessary prior to incorporating it into routine clinical management after SRS for brain metastases.